Between Distancing and Interdependence: The Conflict of Solidarities in the COVID-19 Pandemic. (October 2021) - Basaure, Mauro; Joignant, Alfredo; Mascareño, Aldo
In a bid to contain the spread of COVID-19, different national states around the world have introduced strict measures to regulate social interaction that have affected the interdependence of modern societies. In this article, we argue that this handling of the pandemic produces a conflict of solidarities that can be interpreted by expanding Durkheim's classic formulations (organic and mechanical solidarity) to include the distinction between fragmentary solidarity (based on distancing) and ordinary solidarity (based on empathy and equal treatment). The conflict is triggered precisely by the introduction of fragmentary solidarity. Through this conceptualization, we identify different paradoxes and problems that the pandemic poses for present-day society and analyze how it attempts to overcome them through a generalization of ordinary solidarity. The paper concludes that the conflict of solidarities that characterizes the pandemic is not a passing phenomenon. Its anchorage in the complexity and interdependence of contemporary technological, social, and natural conditions points to its persistence.